Fabrication of slippery textured and slippery non-textured surfaces - Cackovic, Matthew, author; Kota, Arun K., advisor; Popat, Ketul, committee member; Bailey, Travis, committee member (Colorado State University. Libraries, 2018)
Slippery surfaces, i.e., surfaces that have high droplet mobility and low lateral adhesion for liquid droplets, have a wide range of application such as condensation heat transfer, anti-corrosion, lab-on-chip devices, etc. These surfaces can be categorized into smooth slippery surfaces and super-repellant textured slippery surfaces. In this work, we fabricated super-repellant textured superomniphobic paper surfaces. We developed a simple and facile method to fabricate superomniphobic paper surface by growing silicone nanofilaments on a glass microfiber paper surface before imparting low solid surface energy to give the surface the appropriate texture and chemistry. We characterized the performance of our surface and demonstrated our surfaces potential as a lab-on-chip type device. We showed high droplet transport rate, created a simple on-paper pH sensor, demonstrated weight bearing, and showed separation of water from ultra-low surface tension hexane demonstrating the utility of our superomniphobic paper surfaces. We also fabricated a smooth slippery copper surface by creating a chemically and physically homogenous surface. We developed a quick screening test to evaluate the performance of our surfaces in addition to the traditional tests. We showed smoother surfaces performed better and were more slippery.
Keywords: paper; slippery surface; wettability; sliding angle; contact angle hysterisis; superomniphobic